Biosorpsi Krom pada Air Lindi Menggunakan Biomasa Sargassum cinereum - Sri Lestari; Slamet Santoso; Dwi Sunu Windyartini (Fakultas Biologi | Universitas Jenderal Soedirman, 2011)
Leachate is liquid resulted from decomposition of organic waste that contains dissolved and suspended materials as product of microorganism degradation. Leachate comprises high concentration of organic material and heayy metal. High concentration of heavy metal in leachate can be optimally reduced without decreasing organic material concentration through biosorption process. Biosorption is metal binding through adsorption using inactive or dead organism. This research is aimed to perceive the number of biomass, contact duration and combination of the number of biomass and contact duration to adsorb chrome in leachate. Research method employed in this research is experimental method arranged in accordance with Complete Random Design with Split Plot Design. The treatment experimented in this research is contact duration of Sargassum cinereum with leachate as main plot (1 hour, 2 hours and 3 hours) and biomass S. cinereum as sub-plot (200 mg, 300 mg and 400 mg). Data is analyzed using range analysis (ANOVA) and followed by Test of Straight Actual Difference. The result shows that biomass S. cinereum is able to adsorp chrome in leachate. The number of chrome adsorbed in each treatment is different, depend on the contact duration and the number of biomass of S. cinereum.Three hours is optimum contact duration in adsorbing Cr up to 46,275%, meanwhile 400 mg of biomass S. cinereum is optimum concentration to adsorp Cr up to 46,536%. Combination of 3 hours contact duration and 400 mg of biomass S. cinereum could adsorb Cr up to 51,249%.